Self-nanoemulsifying drug delivery system (SNEDDS) of the poorly water-soluble grapefruit flavonoid Naringenin: design, characterization, in vitro and in vivo evaluation. (June 2015) - Khan, Abdul Wadood; Kotta, Sabna; Ansari, Shahid Husain; Sharma, Rakesh Kumar; Ali, Javed
Abstract Naringenin (NRG), predominant flavanone in grapefruits, possesses anti-inflammatory, anti-carcinogenic, hepato-protective and anti-lipid peroxidation effects. Slow dissolution after oral ingestion due to its poor solubility in water, as well as low bioavailability following oral administration, restricts its therapeutic application. The study is an attempt to improve the solubility and bioavailability of NRG by employing self-nanoemulsifying drug delivery technique. Preliminary screening was carried out to select oil, surfactant and co-surfactant, based on solubilization and emulsification efficiency of the components. Pseudo ternary phase diagrams were constructed to identify the area of nanoemulsification. The developed self-nanoemulsifying drug delivery systems (SNEDDS) were evaluated in term of goluble size, globule size distribution, zeta potential, and surface morphology of nanoemulsions so obtained. The TEM analysis proves that nanoemulsion shows a droplet size less than 50 nm. Freeze thaw cycling and centrifugation studies were carried out to confirm the stability of the developed SNEDDS. In vitro drug release from SNEDDS was significantly higher (p < 0.005) than pure drug. Furthermore, area under the drug concentration time-curve (AUC0–24) of NRG from SNEDDS formulation revealed a significant increase (p < 0.005) in NRG absorption compared to NRG alone. The increase in drug release and bioavailability as compared to drug suspension from SNEDDS formulation may be attributed to the nanosized droplets and enhanced solubility of NRG in the SNEDDS.